2022
DOI: 10.1186/s41182-021-00389-x
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine used for the treatment of diarrhea and cough in Kampala city, Uganda

Abstract: Background Globally, diarrheal and respiratory diseases are among the main causes of mortality and morbidity. In Uganda, cities are facing proliferation of trade in herbal medicines (HM), including those for diarrhea and/or cough. Information on the economic, and the ethnopharmacological aspects of these HM is scarce, deterring the sector from achieving optimal capacity to support national development. We profiled the anti-diarrhea and/or anti-cough HM, and the basic economic aspects of HM trad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In contrast, earlier studies in the Kurdistan Region, Iraq, and Indonesia revealed a female predominance in the herbal industry. These ndings may have been in uenced by the cultural contexts of the two studies as well as the nature of the diseases being studied; for instance, their study concentrated on toothpaste herbs, which are more popular among women [33,34]. According to [34] ndings in the Kampala district, the majority of participants elderly( 51 to 55), which is older than the ideal and admirable range of 31 to 45 for the continuation, expansion, and sustainability of the herbal business and endangers its existence [35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, earlier studies in the Kurdistan Region, Iraq, and Indonesia revealed a female predominance in the herbal industry. These ndings may have been in uenced by the cultural contexts of the two studies as well as the nature of the diseases being studied; for instance, their study concentrated on toothpaste herbs, which are more popular among women [33,34]. According to [34] ndings in the Kampala district, the majority of participants elderly( 51 to 55), which is older than the ideal and admirable range of 31 to 45 for the continuation, expansion, and sustainability of the herbal business and endangers its existence [35].…”
Section: Discussionmentioning
confidence: 99%
“…We report a total of sixty-one original scienti c studies that investigated the antibacterial e cacy of E. abyssinica, C. pyrrhopappa, M. foetida, C. citrinus, C. limon, and C. exuosus globally, and published the ndings online from the year 1996 to 2021. The consideration of these plants in this meta-analysis was inspired by their high frequencies of a citation for the treatment of diarrhea and/or cough in Uganda (35)(36)(37)43,44,(113)(114)(115). These species were also found to be used in the management of many more ailments across the world.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them(35,57.4%), were published from the year 2007 to 2017, and the minority in 1996 to 2006 (5, 8.2%). The studies were found in 23 countries across all continents except North America; mostly in Africa and Asia(27,44.3% each) (Fig.2). India had the majority of the eligible studies (14, 23.0%), followed by Cameroon (6, 9.8%), and South Africa (5, 8.2%).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, in Kampala and Kaduna State in Nigeria, respectively, Walusansa et al [30] and Onwudinjo et al [31] noted that the majority of herbalists were older than the desirable age range of 31-45 years, emphasizing this potential risk factor for this industry's demise. In addition, most of the participants had just nished elementary school (X 2 = 66.7805, 95% Cl = 71.474-109.522%, P < 0.0001) and were of low literacy class.…”
Section: Socio-demographic Pro Les Of the Respondentsmentioning
confidence: 99%